DETERMINANTS OF SMALLHOLDER FARMERS’ FOOD SECURITY IN MALI AMIDST CLIMATE CHANGE - Nurjihadi, Muhammad; Guindo, Tidiane (Fakultas Pertanian Universitas Mataram, 2024)
Mali, a West African nation heavily reliant on agriculture, faces significant challenges due to environmental and climatic variations. This paper investigates factors affecting food security among smallholder farmers in the context of climate change. The study employs a mixed-methods approach, utilizing a structured survey of 250 smallholder farmers across eight regions in Mali, complemented by qualitative telephone interviews. The quantitative analysis reveals that government subsidies and climate-related policies do not significantly influence food security perceptions. Similarly, the adoption of climate-resilient agricultural practices, such as drought-tolerant crop varieties and water-saving technologies, shows no strong association with reported food security. However, socio-demographic factors, specifically education level and household size, emerge as critical determinants. The qualitative findings provide nuanced insights into the complexities of government interventions and barriers to the adoption of climate-resilient technologies. This integrated assessment underscores the importance of considering socio-demographic dimensions in crafting effective policies to enhance food security among smallholder farmers in Mali, contributing to the broader discourse on climate change resilience and sustainable agricultural practices.